Droplet activation properties of organic aerosols observed at an urban site during CalNex‐LA. Issue 7 (11th April 2013) - Mei, Fan; Hayes, Patrick L.; Ortega, Amber; Taylor, Jonathan W.; Allan, James D.; Gilman, Jessica; Kuster, William; de Gouw, Joost; Jimenez, Jose L.; Wang, Jian
Abstract : [1] Size‐resolved cloud condensation nuclei (CCN) spectra and aerosol chemical composition were characterized at an urban supersite in Pasadena, California, from 15 May to 4 June 2010, during the CalNex campaign. The derived hygroscopicity ( κ CCN ) of CCN‐active particles with diameter between 97 and 165 nm ranged from 0.05 to 0.4. Diurnal variation showed a slight decrease of κ CCN from 8:00 to 16:00 (from 0.24 to 0.20), which is attributed to increasing organics volume fraction resulted from secondary organic aerosol (SOA) formation. The derived hygroscopicity distribution and maximum activated fraction of the size selected particles were examined as functions of photochemical age. The result indicates that condensation of secondary species (e.g., SOA and sulfate) quickly converted hydrophobic particles to hydrophilic ones, and during daytime, nearly every particle became a CCN at 0.4% in just a few hours. Based on κ CCN and aerosol chemical composition, the organic hygroscopicity ( κ org ) was derived, and ranged from 0.05 to 0.23 with an average value of 0.13, consistent with the results from earlier studies. The derived κ org generally increased with the organic oxidation level, and most of the variation in κ org could be explained by the variation of the organic O : C atomic ratio alone. The least squares fit of the data yielded κ org = (0.83 ± 0.06) × (O:C) + (−0.19 ± 0.02). Compared to previous results based on CCN measurements of laboratory generated aerosols, κ org derived from measurements during the CalNex campaign exhibited stronger increase with O : C atomic ratio and therefore substantially higher values for organics with average O : C greater than 0.5. Key Points: Organic hygroscopicity increases with increasing oxidation level Hydrophobic particles are rapidly converted to hydrophilic ones through aging Greater increase of organic hygroscopicity with O:C based on field measurements